Would You Publish This Book? Material Production, Canadian Criticism, and The Theatre of Form - Lecker, Robert (Studies in Canadian Literature / Études en littérature canadienne, 2000)
The publication of Canadian literary criticism in its historically recognizable forms of academic discourse has dramatically decreased due to shifts in government funding policies and widespread changes in the book publishing industry. The cultural implication of this material shift in the sheer quantity of criticism published is significant: publishers are unreceptive to books about Canadian literature. Decreases in the production of Canadian criticism shift the cultural paradigms by substituting more broadly marketable cultural objects for more esoteric objects aligned with the discourse of nation as it is disseminated through critical acts. With funding from the Ontario Arts Council, the Canada Council and the Aid to Scholarly Publications Program, ECW Press published Ric Knowles's The Theatre of Form and the Production of Meaning: Contemporary Canadian Dramaturgies in 1999 at a financial loss. Most commentary on Canadian criticism does not consider the factors accounting for the material solidity, just as most academics really don't consider the issue of profit or loss associated with the production of the scholarly book as a central factor in the evaluation of the publishability of their scholarly work.